Analysis of Inventory Management with the EOQ Method in Optimizing Fabric Inventory at XYZ Stores - Famelga Clea Putri (PT. SAFARI AMALIA, 2023)
XYZ Store is a company engaged in the textile industry, whose main activity is the production of printed fabrics. The raw materials used in the textile production process are fabrics and in the implementation of the production process these raw materials are always available for the smooth running of the production process. Therefore it is necessary to carry out planning and control of raw materials that are more efficient, then an analysis is carried out using the EOQ method as an option as a comparison between policies that have been implemented so that companies can choose which policy is more efficient in terms of spending on inventory costs or total inventory costs. After doing the calculations, it can be seen that the costs incurred by the company amounted to IDR 7,876,464.1. Meanwhile, the total inventory cost incurred by the company when using the EOQ method is IDR 3,564,927.2. it can be seen that the savings are Rp. 4,311,536.9 when using the EOQ method. While the obstacle in this research is that the EOQ method that has been disclosed by the author in this study cannot be implemented at the XYZ Store due to the agreement factor from the supplier who sends materials once a month. Even though the storage facilities owned by Store XYZ are very adequate, so that the minimum inventory limit that must be stored according to the EOQ calculation can be carried out in field conditions